1991
DOI: 10.1177/026988119100500307
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of a small dose of flumazenil in reversing short-term tolerance to benzodiazepines in normal subjects

Abstract: Twelve normal volunteers received two courses of 7 days of either lorazepam (2 mg every morning; six subjects) or oxazepam (30 mg every morning; six subjects). After one of the courses, 0.2 mg of flumazenil was injected, after the other placebo, using a balanced design and double-blind procedures. A test dose of the lorazepam or oxazepam was administered the day after the flumazenil or placebo. A battery of physiological and psychological tests was applied before and after the dose of benzodiazepine on days 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Among the benzodiazepines, lorazepam has been most extensively studied as an amnesiainducing drug (Satzger et al, 1990;Curran ef al., 1991;Sellers et al, 1992;Greenblatt et al, 1993). In previous studies with lorazepam we found druginduced changes in several ERP subcomponents (Cittadini and Lader, 1991; Allen et af., 1991) but did not attempt to relate these to changes in performance on tasks tapping memory.…”
Section: Introductionmentioning
confidence: 79%
“…Among the benzodiazepines, lorazepam has been most extensively studied as an amnesiainducing drug (Satzger et al, 1990;Curran ef al., 1991;Sellers et al, 1992;Greenblatt et al, 1993). In previous studies with lorazepam we found druginduced changes in several ERP subcomponents (Cittadini and Lader, 1991; Allen et af., 1991) but did not attempt to relate these to changes in performance on tasks tapping memory.…”
Section: Introductionmentioning
confidence: 79%
“…Although a significant reduction in immediate free-recall was observed at peak-plasma concentration of the drug, by the end of the post-treatment session scores of diazepam-treated participants were only marginally and non-significantly worse (p = 0.07) than that of participants treated with placebo, even though the sedative effects of diazepam remained constant until the experiment ended on Day 1. This can be explained by adjustments to some drug effects, or specific acute tolerance to memory effects (see Cittadini & Lader, 1991;Ellinwood, Linnoila, Easler, & Molter, 1983), indicating that people are able to overcome these symptoms, which were much subtler than those on delayed recall.…”
Section: Discussionmentioning
confidence: 99%
“…Although this phenomenon has been tested in BZ-dependent patients with inconsistent efficacy for counteracting tolerance in acute settings (Cittadini and Lader, 1991;Savic et al, 1991;Lader and Morton, 1992), a small clinical study has reported preliminary results on prolonged subcutaneous flumazenil administration in withdrawing BZ-dependent patients (Hulse et al, 2013), suggesting that perhaps longer treatments are needed in human populations. Another study using twice daily intravenous injections of flumazenil showed that flumazenil significantly blocked withdrawal symptoms and kept the patients better in abstinence (Gerra et al, 2002).…”
Section: Effects Of Flumazenil On Benzodiazepine and Alcoholmentioning
confidence: 99%